Factors affecting the success of social marketing: a case of Bangladesh - Mohammad Solaiman (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my